What do pharmacists think about New York State's new nonprescription syringe sale program? Results of a survey - Klein, Susan J. (Springer-Verlag, 2001)
Access to sterile syringes can prevent transmission of blood-borne diseases such as human immunodeficiency virus (HIV) and hepatitis B and C. We conducted a survey of attitudes of pharmacists to aid, in development of the Expanded. Syringe Access Demonstration Program (ESAP) in New York State. ESAP is an HIV prevention initiative that authorizes nonprescription sale of hypodermic needles and syringes by registered pharmacies in New York State beginning January 1, 2001. As part of planning for program implementation, the New York State Department of Health (NYSDOH), in collaboration with the New York State Education Department, conducted a mailed survey of all 4,392 licensed pharmacies in New York State during the summer of 2000. Some surveys (171) were returned as undeliverable. Of the 4,221 eligible respondents, 874 (20.7%) completed surveys were received, of which 574 (65.7%) indicated that their pharmacy would likely participate in ESAP. An additional 11.0% were not sure. Only 139 (15.9%) indicated that they would definitely not participate; 7.4% left this question blank. There were 608 responses to questions on safe disposal practices. Of these, 315 (51.8%) respondents indicated that their pharmacy sold sharps containers, and an additional 29 made them available at no cost. Only 133 (21.9%) respondents to this question did not offer sharps containers and were not interested in doing so. In all, 54 responses indicated that they accepted used hypodernmic needles and syringesfor disposal. Some (170, 28%) that did not accept shaprs for disposal were interested in doing so. More than half (382, 63.0%) did not wish to do so. NYSDOH considered respondent suggestions and minimized ESAP requirements. By March 31, 2001, only 3 months after ESAP became effective, more than half of all licensed pharmacies in New York State were registered for ESAP. Survey results provided useful information to NYSDOH and a good indication of likelihood of registration. The high level of pharmacy participation in ESAP may be reflective of NYSDOH attention to issues raised by pharmacists, as well as the direct effects of outreach to pharmacy chains regarding ESAP.